В пьянящей тишине - Санчес Пиньоль Альберт (Мир Книги, 2006)
Экземпляры: абонемент (20211228) / Инвентарный номер: 48733 / Цена: 50.00 / Сис.шифр: 84(4Ис=Катл)6-44 / Авт.знак: П 32 / ГРНТИ: 17.82.31 / ББК: 84(4Исп)